Impact of Pancreatic Autoantibodies in Pancreas Graft Survival After Pancreas-Kidney Transplantation - Pestana, Nicole (2020)
In simultaneous pancreas-kidney transplantation (SPKT), persistence or recurrence of pancreatic autoantibodies (PAs) has been associated with pancreas graft (PG) autoimmune-driven injury. Our aim was to analyze the impact of PAs on PG survival.Methods. Between January 1, 2000, and December 31, 2017, we studied 139 patients with post-SPKT antieglutamic acid decarboxylase (GAD) autoantibody. Alloimmune (ALI) events were defined as PG rejection and/or de novo donor-specific antibodies (DSA).Hence, 3 groups were defined: patients without ALI events or anti-GAD (n ¼ 42), those with ALI events (n ¼ 14), or those only with autoimmune events (positive for anti-GAD and no ALI events; n ¼ 83). Results. Male sex was predominant (n ¼ 72, 52%). Median age was 35 years (interquartile range: 31-39) and median follow-up was 6-7 years (interquartile range: 4.1-9.2). Regarding anti-GAD positivity post-SPKT (n ¼ 90, 65%), no differences were observed concerning age, sex, anti-HLA antibodies, HLA mismatch number and de novo DSA. ALI events were present in 10% (n ¼ 14). PG survival 15 years post-SPKT was better in patients without immune events (96%) followed by those with ALI (69%) and autoimmune events (63%) (P ¼ .025). Anti-GAD was associated to higher annualized mean Hb1AC (P ¼ .006) and lower mean C-peptide (P ¼ .013). According to pre- and post-SPKT anti-GAD status, conversion from negative to positive was associated to worse (63%) 10-year PG survival (P ¼ .044), compared to persistence of negative (100%) or positive anti-GAD (88%). Anti-islet cell and anti-insulin autoantibodies had no impact. Conclusion. Anti-GAD presence post-SPKT was associated to higher pâncreas disfunction and lower PG survival. De novo anti-GAD seems to offer a particular risk of PG failure.